2014
DOI: 10.1021/jm401764a
|View full text |Cite
|
Sign up to set email alerts
|

Development of Purine-Derived 18F-Labeled Pro-drug Tracers for Imaging of MRP1 Activity with PET

Abstract: Multidrug resistance-associated protein 1 (MRP1) is a drug efflux transporter that has been implicated in the pathology of several neurological diseases and is associated with development of multidrug resistance. To enable measurement of MRP1 function in the living brain, a series of 6-halopurines decorated with fluorinated side chains have been synthesized and evaluated as putative pro-drug tracers. The tracers were designed to undergo conjugation with glutathione within the brain and hence form the correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…choroid plexus, glia cells or brain capillary endothelial cells) has not yet been fully established. Galante and colleagues recently synthesized a 18 Flabeled version of this MRP1 tracer (Galante et al, 2014) for which brain clearance was also shown to be dependent on mMRP1 function.…”
Section: Brain Transportersmentioning
confidence: 99%
“…choroid plexus, glia cells or brain capillary endothelial cells) has not yet been fully established. Galante and colleagues recently synthesized a 18 Flabeled version of this MRP1 tracer (Galante et al, 2014) for which brain clearance was also shown to be dependent on mMRP1 function.…”
Section: Brain Transportersmentioning
confidence: 99%
“…Numerous N-alkylations with [ 18 F]FETos have been performed (Scheme 22). 49,57,[82][83][84][85][86][87][88][89][90][91][92][93][94][95] General reaction conditions involve the use of polar aprotic solvents such as DMSO, DMF or MeCN and temperatures ranging from 82 to 130 1C. Mostly, inorganic bases with a range of different pK a -values were employed depending on the reactivity of the corresponding amine reactant.…”
Section: [ 18 F]fluoroethyl Halides and Sulfonatesmentioning
confidence: 99%
“…However, it is not certain if this innovative approach to measure ABCC1 function can be translated to human subjects, as no clinical application of this PET tracer has been reported yet. Very recently, a fluorine-18-labelled version of this ABCC1 probe has been reported by another research group (Galante et al, 2014). Of course, the most accurate approach for estimating the risk for developing AD would be the direct measurement of Aβ clearance from the AD brain.…”
Section: Abc Transporters – An Outlookmentioning
confidence: 99%